Analysis of Accounting Information System in the Management of Merchandise Inventory at Zeirrie Collection Store - Ok Agam Admar; Nurwani; Nursantri Yanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The Accounting Information System (AIS) is a computer-based system that transforms accounting data into information to support business continuity. Merchandise inventory, as a crucial component, requires proper management since it represents a significant current asset. This study aims to analyze the implementation of AIS in inventory management at Zeirrie Collection Store. The research employed a descriptive qualitative method through observation, interviews, and documentation. The subjects of this study were the owner, warehouse staff, and cashier of Zeirrie Collection Store. The findings indicate that the use of the accounting information system in managing merchandise inventory has not yet been fully optimized. Discrepancies between system data and physical stock were still identified, caused by input errors, manual recording, and weak internal controls. The absence of standard operating procedures (SOPs), unclear division of tasks, and limited employee understanding of the system are identified as inhibiting factors. Thus, the AIS applied has not been fully capable of supporting operational efficiency and inventory information accuracy.